Organoleptic Test Analysis Of Pandan Cake Using A Gas Oven And Convection Oven - Ertanto, Boby; Siregar, Juliana; Elida, Elida; Anggraini, Ezi (Universitas Negeri Padang, 2024)
This research was motivated by the use of a gas oven which is more efficient compared to a convection oven. The aim of the research was to compare the quality of pandan sponge cake using a gas oven and a convection oven. This type of research is pure experiment using the Independent Sample T-test method. The research instrument was carried out by providing an organoleptic test format to the panelists. The data obtained was then tabulated in tabular form and a level test was carried out on each variable X1 and X2 to find out whether there was a quality comparison for these variables. The results of the research show that there is no significant influence on the quality of the shape, color, aroma, texture and taste of pandan cake. For the quality of the shape (round) it has an average value of X1 (3.15) and X2 (2.89), for color quality (brownish green for the outside) has an average of X1 (2.83) and X2 (3.01), for color (green inside) has an average of X1 (3.03) and ), then for the quality of aroma (fragrant pandan leaves) has an average of X1 (3.19) and X2 (3.31), while the average value for texture quality (soft) has an average of and X2 (2.84), and for taste quality (sweet) it has an average value of X1 (3.06) and 87) and X2 (3.07).